Boosting the VZV-Specific Memory B and T Cell Response to Prevent Herpes Zoster After Kidney Transplantation - Kho, Marcia M. L.; Weimar, Willem; Malahe, S. Reshwan K.; Zuijderwijk, Joke M.; de Kuiper, Ronella; Boer-Verschragen, Marieken J.; Eijk, Annemiek A. van der; Hesselink, Dennis A.; Reinders, Marlies E. J.; van Besouw, Nicole M. (Frontiers in Immunology, 2022)
Background: Solid organ transplant recipients are at high risk to develop (complicated) herpes zoster (HZ). Booster vaccination could prevent HZ. However, end-stage renal disease (ESRD) patients show poor immunological responses to vaccinations. We studied the effect of a live attenuated VZV booster vaccine on VZV-specific B and T cell memory responses in ESRD patients and healthy controls. NL28557.000.09, www.toetsingonline.nl Methods: VZV-seropositive patients, aged ≥50 years, awaiting kidney transplantation, were vaccinated with Zostavax®. Gender and age-matched VZV-seropositive potential living kidney donors were included as controls. VZV-specific IgG titers were measured before, at 1, 3 and 12 months post-vaccination. VZV-specific B and T cell responses before, at 3 months and 1 year after vaccination were analysed by flow-cytometry and Elispot, respectively. Occurrence of HZ was assessed at 5 years post-vaccination. Results: 26 patients and 27 donors were included. Median VZV-specific IgG titers were significantly higher at all time-points post-vaccination in patients (mo 1: 3104 IU/ml [1967-3825], p<0.0001; mo 3: 2659 [1615-3156], p=0.0002; mo 12: 1988 [1104-2989], p=0.01 vs. pre: 1397 [613-2248]) and in donors (mo 1: 2981 [2126-3827], p<0.0001; mo 3: 2442 [2014-3311], p<0.0001; mo 12: 1788 [1368-2460], p=0.0005 vs. pre: 1034 [901-1744]. The patients’ IgG titers were comparable to the donors’ at all time-points. The ratio VZV-specific B cells of total IgG producing memory B cells had increased 3 months post-vaccination in patients (0.85 [0.65-1.34] vs. pre: 0.56 [0.35-0.81], p=0.003) and donors (0.85 [0.63-1.06] vs. pre: 0.53 [0.36-0.79], p<0.0001) and remained stable thereafter in donors. One year post-vaccination, the percentage of CD4+ central memory cells had increased in both patients (0.29 [0.08-0.38] vs. 0.12 [0.05-0.29], p=0.005) and donors (0.12 [0.03-0.37] vs. 0.09 [0.01-0.20], p=0.002) and CD4+ effector memory cells had increased in donors (0.07 [0.02-0.14] vs. 0.04 [0.01-0.12], p=0.007). Only 1 patient experienced HZ, which was non-complicated. Conclusion: VZV booster vaccination increases VZV-specific IgG titers and percentage VZV-specific memory T-cells for at least 1 year both in ESRD patients and healthy controls. VZV-specific memory B cells significantly increased in patients up to 3 months after vaccination. Prophylactic VZV booster vaccination prior to transplantation could reduce HZ incidence and severity after transplantation.